Ultrafast nonlinear optical response in solution dispersions of black phosphorus - Lili Miao (Nature Portfolio, 2017)
Abstract We report the spatial self-phase modulation (SSPM) effect for solution dispersions of black phosphorus (BP). The experimental results suggest that this concentration-dependent coherent light diffraction is due to the ultrafast and large third-order optical nonlinearity of BP. The third-order nonlinear susceptibility of BP has been simply obtained about 10−19 m2/V2 by analyzing the experimental results. The fast relaxation time during dynamic relaxation is obtained as 0.13 ps. Our experimental results imply novel potential application of BP in ultrafast nonlinear phase modulation devices based on their nonlinear optical response.